Modification of titanium orthopedic implants with bioactive glass: a systematic review of in vivo and in vitro studies - Liang, Jin; Lu, XinYue; Zheng, XinRu; Li, Yu Ru; Geng, XiaoYu; Sun, KeXin; Cai, HongXin; Jia, Qi; Jiang, Heng Bo; Liu, Kai (Frontiers in Bioengineering and Biotechnology, 2023)
Bioactive glasses (BGs) are ideal biomaterials in the field of bio-restoration due to their excellent biocompatibility. Titanium alloys are widely used as a bone graft substitute material because of their excellent corrosion resistance and mechanical properties; however, their biological inertness makes them prone to clinical failure. Surface modification of titanium alloys with bioactive glass can effectively combine the superior mechanical properties of the substrate with the biological properties of the coating material. In this review, the relevant articles published from 2013 to the present were searched in four databases, namely, Web of Science, PubMed, Embase, and Scopus, and after screening, 49 studies were included. We systematically reviewed the basic information and the study types of the included studies, which comprise in vitro experiments, animal tests, and clinical trials. In addition, we summarized the applied coating technologies, which include pulsed laser deposition (PLD), electrophoretic deposition, dip coating, and magnetron sputtering deposition. The superior biocompatibility of the materials in terms of cytotoxicity, cell activity, hemocompatibility, anti-inflammatory properties, bioactivity, and their good bioactivity in terms of osseointegration, osteogenesis, angiogenesis, and soft tissue adhesion are discussed. We also analyzed the advantages of the existing materials and the prospects for further research. Even though the current research status is not extensive enough, it is still believed that BG-coated Ti implants have great clinical application prospects.